Customer management in Internet-based platform firms: review and future research directions. Issue 7 (18th May 2020) - Yang, Zhi; Diao, Zihe; Kang, Jun
Abstract : Purpose: This study proposes a conceptual framework for analyzing customer management strategies and their effects on Internet-based platform performance based on a review of the relevant literature, and provides directions for future research. Design/methodology/approach: A literature review of relevant research articles on customer management in platform firms was conducted. Findings: First, a framework based on the market maker view of platform firms suggests customer acquisition, customer retention and customer governance are the main customer management subprocesses toward improving platform firm performance. Second, the most studied customer management strategies for each subprocess contribute to platform performance based on the mechanisms of building customer network, developing customer network effect and managing sustainable customer networks. Originality/value: This study proposes a framework that identifies customer acquisition, customer retention and customer governance as three key customer management subprocesses in platform firms. It also summarizes the most studied customer management strategies/actions for each subprocess. With this analytical framework, it identifies underexplored key issues in customer management for further research.